Техніко-криміналістичне забезпечення діяльності захисника у кримінальному провадженні - Гусєва, В. О.; Husieva, V. O.; Коломойцев, М. М.; Kolomoitsev, M. M.; Vlada Husieva (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 1 (108), ч. 1. - С. 275-284, 2025)
У статті сформульовано визначення поняття «техніко-криміналістичне забезпеченням діяльності захисника у кримінальному провадженні», під яким запропоновано розуміти систему правових, організаційних, науково-технічних положень і прикладних заходів щодо розроблення, впровадження та практичного використання технічних засобів з метою здійснення захисту за призначенням, досягнення цілей слідчих (розшукових) і процесуальних дій, огляду та фіксації цифрових доказів. Встановлено, що за загальним правилом чинне законодавство не забороняє захисникові використовувати техніко-криміналістичні засоби під час участі у слідчих (розшукових) і процесуальних діях. Водночас про факти їх застосування захисник має попередити всіх учасників такого заходу, а сторона обвинувачення за наявності для цього об’єктивних підстав хоча і може заборонити їх використання, однак здійснює це лише на підставі вмотивованої постанови, а слідчий суддя, суд – на підставі ухвали. Визначено окремі аспекти використання технічних засобів під час збирання доказів.

The article determines that technical and forensic support of a defence counsel’s activities in criminal proceedings should be understood as a system of legal, organisational, scientific and technical provisions and applied measures for the development, implementation and practical use of technical means for the purpose of providing defence as intended, achieving the objectives of investigative ( search) and procedural actions, examination and recording of digital evidence. It is established that, as a general rule, current legislation does not prohibit the defence counsel from using technical and forensic means while participating in investigative (search) and procedural actions, at the same time, the defence counsel must notify all the participants of such an event of all the facts of their use, and the prosecution party, if there are objective grounds for this, although it may prohibit their use, but may do so only on the basis of a reasoned resolution, the investigating judge, the court – the ruling. It is well-grounded that the defence counsel has the right to choose the technical means which he/she plans to use for the purposes of defence, but the analysis of law enforcement practice allows to state that the most typical ones are: mobile phones for photo and video recording, making photocopies of procedural documents, material evidence, recording the procedural action; cameras for making copies of procedural documents, including during the familiarization with the criminal proceedings; video cameras for recording the procedure for conducting investigative (search) and other procedural actions; computer facilities for reviewing and making copies of digital traces and evidence, familiarising themselves with case files received in the “E-Court” system, and ensuring the electronic document control. We believe that the prospects for future research are to identify specific practical recommendations for the collection of evidence by a defence counsel, taking into account the characteristics of specific objects.
Technical and forensic support of a defence counsel in criminal proceedings
Keywords: кримінальне провадження; захисник; збирання доказів; слідча (розшукова) дія; технічні засоби; техніко-криміналістичний засіб; криміналістична техніка; criminal proceedings; defence counsel; collection of evidence; investigative (search) action; technical means; technical and forensic means; forensic technique